2013
DOI: 10.1515/jbcpp-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the hypoglycemic effect of soft drink leaf extract of Phyllanthus amarus (Euphorbiaceae) in rats

Abstract: The results from this study may have validated the traditional basis for the use of P. amarus as antidiabetic agent with the pharmacological activities attributed to the presence of flavonoids and other phenolics contained in this plant. At the doses used, SDE also appeared safer than glibenclamide even though the latter is more potent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Hypoglycaemic effects have been reported for some plants that contain flavonoids (Adedapo & Ofuegbe, 2014;Juárez-Reyes et al, 2015;Liu et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycaemic effects have been reported for some plants that contain flavonoids (Adedapo & Ofuegbe, 2014;Juárez-Reyes et al, 2015;Liu et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Higher sperm count, percentages of sperm forward motility, viability and HOS tail-coiled with lower percentage of abnormal sperm were observed following C. borivilianum root extract treatment to STZ-induced diabetic rats. Administration of the root extract also lower the percentage of sperm with abnormal appearances, and in few occasion, the herbal root extract effect exceeds glibenclamide, a reference anti-diabetic drug [43]. Our findings have further shown that C. borivilianum root extract was able to lower the level of sperm oxidative stress as evident from lower amount of lipid peroxidation product, MDA, tissue superoxide and nitric oxide free radicals and higher amount of total antioxidant capacity (TAC) and levels of endogenous antioxidant enzymes (SOD, CAT and GPx) in the sperm of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Phyllanthus amarus belongs to the Euphorbiaceae family, which has been used to treat problems related to the genitourinary tracts [ 47 ]. Recent studies have also revealed antidiabetic activity of this extract [ 26 , 48 ]. It is notable that Phyllanthus amarus exhibit considerable α-amylase inhibitory activities, which may suppress postprandial glucose [ 27 ].…”
Section: Discussionmentioning
confidence: 99%